IMPLEMENTASI TEORI BEHAVIORISME DALAM MEMBENTUK DISIPLIN SISWA SDN CIPINANG BESAR UTARA 04 PETANG JATINEGARA JAKARTA TIMUR - Sugi Harni; Indina Tarjiah (Universitas Muhammadiyah Surakarta, 2018)
The objective of this research is to know the extent of the behaviorism theory has an impact in forming discipline in elementary school students, especially at SDN Cipinang Besar Utara 04 Petang in Kelurahan Cipinang Besar Utara Jatinegara Sub-district, East Jakarta. This research adopted qualitative approach with descriptive method. This research was obtained by using several assessment in the form of observation, interview, and documentation. Analysis techniques data used by collecting information from the data that has been obtained from the assessment that has been used, provides data, and concluded the data. The results of this research showed that the implementation of consistent behaviorism theory can form discipline to their students.